Gambaran Kasus Dan Evaluasi Sistem Surveilans ISPA Di Puskesmas Perumnas Periode Agustus Sampai Oktober Tahun 2025 - La Ode Liaumin Azim (STIKES Columbia Asia Medan, 2026)
Acute Respiratory Infections (ARI) remain one of the public health problems that contribute significantly to high morbidity rates, especially among vulnerable groups. Community health centers, as primary health care facilities, play an important role in recording, reporting, and monitoring cases through surveillance systems. This study aims to determine the description of ARI cases and evaluate the implementation of the ARI surveillance system at the Perumnas Community Health Center from August to October 2025. This study uses a descriptive evaluative approach. The surveillance system evaluation is based on the 5M components, namely man, money, material, method, and machine. Data were obtained through a review of surveillance documents and observation of the implementation of the ARI case recording and reporting system at the health center. The results of the study indicate that ARI is still one of the most common diseases found in the Perumnas Community Health Center's working area. The implementation of ARI surveillance is generally running well, but there are still several obstacles in terms of human resources, supporting facilities, data completeness, and optimization of reporting methods. These conditions affect the quality of the epidemiological information produced. Therefore, it is necessary to strengthen the surveillance system by increasing the capacity of officers, providing supporting facilities, and improving recording and reporting mechanisms so that the implementation of ARI surveillance is more effective and supports disease control efforts.